Sombart's die Drei Nationalokonomien - Clark, J. M.; Sombart, Werner (Quarterly Journal of Economics, 1931)
Journal Article Sombart's Die Drei Nationalökonomien Get access J. M. Clark J. M. Clark Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 45, Issue 3, May 1931, Pages 517–521, https://doi.org/10.2307/1883902 Published: 01 May 1931